Routine Fixation of Weber B Fibula Fractures with a Lateral Locking Plate and No Lag Screw. Issue 4 (22nd October 2020) - Bohl, Daniel D.; Mehraban, Nasima; Foran, Ian; Hamid, Kamran S.
Category: Ankle Introduction/Purpose: The current standard of care for management of an unstable ankle fracture that includes an oblique Weber B fibula fracture is open reduction and internal fixation (ORIF) using a plate and screws to anatomically reduce and compress the fractured fibula. The most popular first-line techniques include either a lag screw with neutralization plate or an anti- glide plate with or without a lag screw through the plate. However, these techniques can be technically challenging in osteoporotic bone or within fibulas of smaller diameter, and in some cases can result in fragmentation at the fracture site. The purpose of this study is to examine an alternative first-line method for routine treatment of Weber B fibula fractures. Methods: Fifty-two patients undergoing ORIF of a Weber B fibula fracture by a single surgeon were included in this retrospective study. In every case, reduction and clamping of the fracture was attempted. If successful, a lateral locking plate was slid underneath the clamp(s) and applied with cortical screws proximally and locking screws distally. If clamping was unsuccessful, length/alignment/rotation was achieved by alternative methods (i.e. push-pull technique, use of plate to reduce fracture, etc.), and a lateral locking plate was ultimately applied in a similar manner. No screw crossed the fracture in any case. Per published precedent, nonunion was defined as either a gap of >3mm between fracture surfaces >6 months postoperatively or a fracture line >2-3 mm wide and sclerosing of the fracture surfaces >6 months postoperatively. Similarly, malunion was defined as >=1 of the following: talar tilt >2 degrees, talar subluxation >2 mm, or tibiofibular clear space >=5 mm. Results: The mean (+- standard deviation) age of the 52 included patients was 44.2 +- 16.2 years, the mean body mass index was 27.7 +- 6.6 kg/m2, and 63.5% of patients identified themselves as female. The mean follow-up was 6.2 +- 4.4 months. In addition to undergoing fixation of the lateral malleolus, 21 patients also underwent fixation of the posterior malleolus, 27 underwent fixation of the medial malleolus, 29 underwent fixation across the syndesmosis, and seven underwent repair of the deltoid. In all patients, bony anatomic union of the fibula and congruence of the mortise were achieved, with no cases of malunion or nonunion. Conclusion: Routine fixation of Weber B fibula fractures with a lateral locking plate and no lag screw is an alternative method to treat Weber B fibula fractures with excellent radiographic results.